Exploring Child Grooming Sexual Abuse through Differential Association Theory: A Criminological and Legal Examination with Constitutional Implications - Utari, Indah Sri; Arifin, Ridwan; Ramada, Diandra Preludio (Faculty of Sharia, Universitas Islam Negeri (UIN) Profesor Kiai Haji Saifuddin Zuhri Purwokerto, Indonesia, 2024)
The rapid evolution of technology, particularly the ubiquitous presence of the internet, has brought about significant societal changes. While technological advancements have brought numerous benefits, they have also introduced new challenges and risks. Among these challenges is the alarming rise of child grooming, a form of sexual harassment perpetrated against minors, facilitated by the online environment. In Indonesia, the incidence of child grooming is increasingly prevalent, with several reported cases highlighting its emergence as a pressing societal issue. However, the absence of specific legal frameworks addressing this crime has posed significant challenges for law enforcement authorities tasked with its prevention and prosecution. The lack of dedicated legislation targeting child grooming underscores the need for a comprehensive legal response to effectively combat this form of exploitation. Currently, law enforcement officials rely on discretion in the absence of specific legal provisions, resulting in ad-hoc approaches to addressing these cases. This paper employs a normative juridical approach, utilizing The Statute Approach, to examine the legal landscape surrounding child grooming in Indonesia. By synthesizing existing literature and statutory regulations, this study aims to shed light on the legal complexities inherent in combating this emerging crime. In conclusion, while child grooming remains a relatively new phenomenon in Indonesia, its detrimental impact on minors necessitates urgent legislative action. By enacting dedicated laws and policies, the Indonesian government can provide law enforcement agencies with the necessary tools to effectively address and mitigate the prevalence of child grooming, ensuring the protection and well-being of the nation's youth.